2020
DOI: 10.3390/su12166445
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of the Sustainable Development Goals (SDGs): Does Performance on the SDGs Affect Re-Election?

Abstract: While the economic voting hypothesis is a well-researched approach to explain behavior at the ballot box, a broader perspective of economic, social and environmental issues regarding a government’s chances to get re-elected is still missing in the literature. In this context, this paper makes use for the first time of the Agenda 2030 with its 17 Sustainable Development Goals (SDGs) as the comprehensive policy framework that all 193 UN member states have pledged to achieve. The objective of our study is therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Explorations of how policy interacts with the SDGs have also been offered. Kroll and Zipperer (2020) identified that government performance concerning the pursuit of SDG5 correlates with the likelihood of being re-elected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Explorations of how policy interacts with the SDGs have also been offered. Kroll and Zipperer (2020) identified that government performance concerning the pursuit of SDG5 correlates with the likelihood of being re-elected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Migration is a significant issue today, and immigrant countries are trying to manage this process and its consequences as best they can. The United Nations 2030 SDGs provide a roadmap to address a wide range of global challenges, including migration-related areas, to create a more equitable, happy, and environmentally sustainable global community [1]. The SDGs serve as guidelines for raising prosperity in countries and creating happier societies.…”
Section: Introductionmentioning
confidence: 99%